STIMULASI PENGEMBANGAN KECERDASAN VERBAL-LINGUISTIK ANAK USIA DINI MELALUI METODE PEMBELAJARAN PAUD - Dwi Haryati (Jurusan PGMI FTIK IAIN Metro Lampung, 2017)
Everyone has their own intelligence on him. The scale of intelligence that has been used has many limitations so that it can not predict a successful performance in one's future. Intelligence possessed by a person needs to get attention in providing stimulation so as to develop optimally. Each individual has a different way of developing the various intelligences. That's why in the process of education and learning, especially every child must get different treatment according to the potential of intelligence that exist in each self. A person with high verbal linguistic intelligence can pay attention to a suitable language mastery. The storytelling method, the singing method, the role playing method, and the method of conversation are methods that can be done by the teacher in stimulating the verbal-linguistic intelligence of early childhood